Metaforyzacja mitu w literaturze Rzymu późnorepublikańskiego. Na przykładzie Endymiona - Pierzak, Damian (Symbolae Philologorum Posnaniensium Graecae et Latinae, 2016)
In Roman republican literature the Endymion figure, not unlike other mythical characters, carries a message which becomes apparent only when properly deciphered. For that reason its meaning can be made out best by being looked at from a rhetorical perspective.